2023
DOI: 10.1088/1361-6463/acb71f
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic skyrmion dynamics induced by surface acoustic waves

Abstract: Magnetic skyrmions are promising information carriers for high-density memories. The dynamical motion of magnetic skyrmions have been extensively investigated in the development of magnetic racetracks. In this study, a surface acoustic wave (SAW) is theoretically investigated to drive skyrmions by using micromagnetic simulations. The in-plane type and out-of-plane displacement components of SAWs generate different magnetoelastic effective fields. The shear horizontal (SH) wave mode SAW drives skyrmions flow mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The manipulation of skyrmion dynamics by acoustic wave could potentially lead to skyrmion-based memory, logic and microwave devices without involving electric currents and with designed motion trajectory (circular motion, Supplementary Fig. S13 ) 47 . For a simple comparison, the efficiency of different skyrmion-driven methods is provided in Supplementary Table.…”
Section: Discussionmentioning
confidence: 99%
“…The manipulation of skyrmion dynamics by acoustic wave could potentially lead to skyrmion-based memory, logic and microwave devices without involving electric currents and with designed motion trajectory (circular motion, Supplementary Fig. S13 ) 47 . For a simple comparison, the efficiency of different skyrmion-driven methods is provided in Supplementary Table.…”
Section: Discussionmentioning
confidence: 99%
“…Quantum coherence phenomena in semiconductors have also been the subject of extensive research. In particular, quantum structures such as quantum dots or wells have demonstrated the ability to control the band gap by altering their geometry [30][31][32][33][34]. This feature makes these structures highly customizable, serving as artificial atoms with potential applications in optoelectronics and quantum information technology.…”
Section: Introductionmentioning
confidence: 99%
“…18 The dynamic strain induced by surface acoustic waves (SAWs) has also been suggested as an attractive approach to control thin film magnetization. [19][20][21][22][23][24][25][26][27][28][29][30][31] In particular, Yokouchi et al experimentally observed the creation of skyrmions by SAWs in a Pt/Co/Ir thin film owing to the inhomogeneous effective torque arising from both SAWs and thermal fluctuations via magnetoelastic coupling. 32 Nepal et al theoretically studied the dynamical pinning of skyrmion bubbles at the anti-nodes of standing SAWs in a FePt nano-wire, revealing the strain gradient induced by SAWs is the driving force for skyrmion motion.…”
mentioning
confidence: 99%